Taxonomic revision of the Neotropical genus Himantigera James, 1982 (Diptera: Stratiomyidae: Sarginae), including the description of two new species and a key to the known species - Fachin, Diego Aguilar; Hauser, Martin (Zootaxa, 2018)
The Neotropical genus Himantigera James in James & McFadden, 1982, is revised. Two new species are described and illustrated—H. amauroptera nov. sp. (Costa Rica, Panama, Colombia), and H. xanthopoda nov. sp. (Mexico, Nicaragua, Costa Rica). Three species are transferred from Himantigera to Sargus Fabricius, 1798—S. dichrous (Schiner, 1868) comb. nov., S. flavoniger Lindner, 1928 comb. rev. and S. fulvithorax (Bigot, 1879) comb. nov. One species is transferred to Microchrysa Loew, 1855—M. splendens (Schiner, 1868) comb. nov. Himantigera jamesi Lindner, 1969 syn. nov. is proposed as a junior synonym of H. superba Lindner, 1949. The type species H. silvestris McFadden, 1982, as well as H. nigrifemorata Macquart, 1847 and H. superba Lindner, are herein redescribed and illustrated. Photographs of the type specimens of these three species are provided. Two unnamed species of Himantigera (sp. A and sp. B) are also described given that they have slight differences, but because we had only one specimen of each species, we did not officially describe them. This updates the total number of extant Himantigera from eight sensu Woodley (2001) to seven species. The species Merosargus apicalis Lindner, 1935, although never referred to the genus Himantigera or Himantoloba McFadden 1970, is also transferred to the genus Sargus. A key to all species of Himantigera and a map expanding geographical distribution of the genus are also presented, with the first records of the genus for Nicaragua, Colombia, Venezuela, Trinidad and Tobago, Ecuador and Bolivia.